2018
DOI: 10.12669/pjms.342.14002
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic Trans-Sphenoidal surgery: Efficacy and response in pituitary adenoma

Abstract: Objectives:The purpose of the study was to access the efficacy and response of the endoscopic transsphenoidal surgery in pituitary adenomas.Methods:It was descriptive case study, conducted at Neurosurgery Department in collaboration with the Endocrine Unit (Medical Unit-II) Of Jinnah Post Graduate Medical Center Karachi from January 2015 to July 2017. Patients with sellar, supra sellar and para sellar tumors were enrolled in the study. Patients with prolactinoma and recurrent pituitary tumors were excluded. Da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(23 citation statements)
references
References 20 publications
1
22
0
Order By: Relevance
“…Pituitary adenomas account for 8-15% of intracranial tumors (21). These tumors are mainly treated through a combination of surgery and medicine (5,22). Most patients with pituitary adenoma require long-term drug treatment after undergoing surgery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pituitary adenomas account for 8-15% of intracranial tumors (21). These tumors are mainly treated through a combination of surgery and medicine (5,22). Most patients with pituitary adenoma require long-term drug treatment after undergoing surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Functional pituitary adenomas can lead to elevated secretion of 1 or multiple hormones, while nonfunctional adenomas compress the areas surrounding the anterior pituitary, resulting in hormonal deficiencies (3,4). Transsphenoidal surgery is the first-line treatment for pituitary adenomas (5). However, surgery entails great psychological pressure as well as physical discomfort, which can deteriorate patients' social psychological state.…”
Section: Introductionmentioning
confidence: 99%
“…Considering this option, some clinical and economic results have shown that surgical resection costs mirror the costs of medical therapy over a 10-year period, after which TSS might be considered more cost effective for perhaps young patients with microadenomas [8,37]. Complication rates with TSS are minimal [38], though surgical outcome is very dependent upon the skill and experience of the surgeon as well as the size of the tumor and baseline serum PRL levels, with gross total removal achieved in 18-75 % of patients [38,39]. Patients with microprolactinomas are shown to have a higher rate of normalizing serum PRL levels post-surgery, at 75-90 % versus 33-50 % of patients with macroprolactinomas [1,4,9,27].…”
Section: Continuedmentioning
confidence: 99%
“…Patients with microprolactinomas are shown to have a higher rate of normalizing serum PRL levels post-surgery, at 75-90 % versus 33-50 % of patients with macroprolactinomas [1,4,9,27]. However, recurrence rates of hyperprolactinemia can be observed if there was no gross total resection [39] or if patients had large tumors [25]. Recurrence of hyperprolactinemia may occur in 18-22 % of patients after initial normalization [4,9,27].…”
Section: Continuedmentioning
confidence: 99%
“…The prevalence of complications after endoscopic TSS has been reported between 3 -36%, which are mostly due to the CSF leak, dysfunction of the anterior lobe, and diabetes insipidus (DI). [3][4] Rehman et al (2018) 4 reported around 31% complications from TSS.…”
Section: Introductionmentioning
confidence: 99%